Consumer Preference Analysis of Snack Bar Product Attributes in Surabaya Using Conjoint Analysis Method - Herdianto, Ferly Wirawan; Yulistiani, Ratna; Sarofa, Ulya (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study examines consumer preferences for snack bar attributes in Surabaya using the conjoint analysis method. The research aims to identify key product attributes that influence purchasing decisions and provide recommendations for manufacturers to develop healthier snack bar products. Data were collected through a survey of 100 purposively selected respondents. The study analyzed attributes such as flavor, texture, composition, packaging, weight, and price, evaluating 16 stimulus combinations using a Likert scale. The findings indicate that consumers prefer snack bars with a sweet taste, sticky texture, single-pack packaging, a weight of 25 grams, and a price above Rp10,000. Conjoint analysis reveals that price and taste exert the greatest influence on consumer preferences. These insights offer valuable guidance for snack bar manufacturers in optimizing product development and enhancing market competitiveness. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-being SDG 9: Industry, Innovation, and Infrastructure SDG 12: Responsible Consumption and Production